Analysis of the movements generated by a multi‐field functional electrical stimulation device for upper extremity rehabilitation. Issue 10 (29th June 2022) - Martín‐Odriozola, Aitor; Rodríguez‐de‐Pablo, Cristina; Caceres‐Salegi, Ane; García‐Calleja, Andrea; Marín‐Ojea, Juan Ignacio; Hernández, Erik; Imatz‐Ojanguren, Eukene; Keller, Thierry; Zabaleta‐Rekondo, Haritz
Abstract: Background: The most common chronic sequela after stroke is the loss of arm function, and functional electrical stimulation (FES) applied to the forearm muscles is one of the options to treat it. Surface multi‐field electrodes have emerged, showing a great potential to improve the selectivity of the stimulation, delay muscle fatigue, and provide easier donning and doffing. The muscular selectivity takes on special relevance in the rehabilitation of the upper extremity as hand dexterity requires a wide diversity of specific muscle actions. Methods: This pilot study analyses the movements generated in the wrist and fingers using a commercial multi‐field technology‐based FES device (Fesia Grasp). The study included five patients with hemiplegic subacute stroke, in which scanning of all cathodes of the electrode was carried out daily for 5 days, in two different forearm positions, with the resulting movements being labeled by experienced therapists. Results: The aim of this pilot study was to determine if there were differences between subjects and between forearm positions in terms of produced movements. Movements of the wrist (two movements) and the fingers (six movements) could be achieved in two different forearm positions. Conclusions: The multi‐field electrode of Fesia Grasp enables to generate a wide range of movements of the hand in different positions. This fact could allow to produce more physiological movement patterns during the rehabilitation process with FES, which could have a beneficial effect on the recovery of patients with neurological diseases. Abstract : This study analyses the movements generated in the wrist and fingers using a multi‐field technology‐based FES device in five persons with subacute stroke. Scanning of all cathodes of the electrode was carried out daily for 5 days, in two different forearm positions (neutral [A], pronated [B]), and the resulting movements were labeled by experienced therapists. Results show that eight different movements of the hand can be achieved in the two positions (Fig.), but no statistically significant differences were found between them.